Analysis of Character Education Strengthening Program Management In SMP Muhammadiyah 3 Depok - Azhar Basyir (Edification Journal : Pendidikan Agama Islam, 2020)
This studies describe the management of character education strengthening program (PPK) at SMP Muhammadiyah 3 Depok. The types of this research is descriptive-qualitative. the techniques of data collections using observation, interviews, and documentation. The results of this study are (1) The activities of PPK include flag ceremonies, 7S (senyum-smile, salam-peace in greetings, sapa-greetings, sopan-respectful, santun-courtesy, sigap-enthusiasm), (2) The management of the PPK program runs with a good formulation and has clear purpose. (3) Supporting factors for this program are adequate facilities and infrastructures, the presence of adequate and militant young teaching staff, principals who are classified as young and have a good work ethic.